The role of HBD-2, HBD-3, and calprotectin in the relationship between chronic periodontitis and atherosclerosis - Taspinar, Mehmet; Bozoglan, Alihan; Ertugrul, Abdullah Seckin; Elmas, Levent (Tech Science Press, 2020)
This study was carried out to compare individuals diagnosed with atherosclerosis and periodontal periodontitis based on the degree of change in the human beta-defensins (HBD) HBD-2, HBD-3, and calprotectin. Atherosclerosis is the most frequently observed cardiovascular disease. Dental and periodontal infections are known to provide a considerable basis for atheroma plaque formation. The study group consists of a total number of 40 subjects, with 20 patients diagnosed with atherosclerosis and chronic periodontitis and 20 systemically healthy patients diagnosed with chronic periodontitis. Clinical periodontal and blood parameters and HBD-2, HBD-3, and calprotectin biomarkers in the gingival crevicular fluid were measured. In both groups, following clinical periodontal treatment, a statistically significant decrease in white blood cells (WBC), low-density lipoproteins (LDL), fibrinogen, creatinine, and platelets (PLT), a statistically significant increase in high-density lipoproteins (HDL) in blood samples, statistically meaningful decrease in HBD-2, HBD-3, and calprotectin in the gingival crevicular fluid were achieved. Blood values and HBD-2, HBD-3, calprotectin amounts in the gingival crevicular fluid were increased significantly in the test group compared to the control group. A positive correlation was observed between decreases in HBD-2, HBD-3, calprotectin, and clinical periodontal indices. Regression in systemic inflammation was observed after clinical periodontal treatment. It is concluded that nonsurgical periodontal treatment of chronic periodontitis positively affects atherosclerosis prognosis.
Keywords: Atherosclerosis; Periodontal Diseases; HBD-2; HBD-3; Calprotectin